Senegal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper assesses the extent to which accounting for losses of pubic enterprises (PEs), fiscal risks of public-private partnerships (PPPs), and government support to private enterprises would change Senegal's fiscal deficit. It analyzes SENELEC's (electricity company) financial position, and discusses the potential risks that PPPs can pose in Senegal. It examines export competitiveness and the exchange rate in Senegal. The paper also documents the performance of the export sector in Senegal, and assesses the reasons for the lackluster performance of the export sector.